Prosedur Pelayanan Customer Service Pada PT Bank Rakyat Indonesia Unit Cijeruk - Tantonio, Michael Claudius; Fadillah, Adil; Sulistiono, Sulistiono (Program Vokasi dan LPPM IBI Kesatuan, 2024)
Customer Service is an art that combines human emotions, behavior, understanding, feelings, and impressions from the customer's point of view. Customer satisfaction will increase through the provision of good service, thus making customers loyal and having a positive impact on the business. which makes customers use the company's products and services repeatedly and contributes to the profit desired by the business at the bank.The purpose of this discussion is to understand Customer Service services provided to customers, know the problems or obstacles faced and understand the alternatives in dealing with obstacles.The results of this discussion indicate that the services provided to customers when performing services have been carried out in accordance with procedures, the services provided have met the needs and expectations of customers. There are obstacles from banks and customers, from the bank, namely the Internet network provided sometimes errors, from customers, namely different customer characters, little customer knowledge about the terms of management, and not completing the requirements. The alternative is to improve and update facilities and systems, and explain to customers based on the regulations that apply to the company. Keywords: Service, Customer Service